Free vibration analysis of beams by using a third-order shear deformation theory - Simsek, Mesut; Kocatuerk, Turgut (SPRINGER INDIA, 2007)
In this study, free vibration of beams with different boundary conditions is analysed within the framework of the third-order shear deformation theory. The boundary conditions of beams are satisfied using Lagrange multipliers. To apply the Lagrange's equations, trial functions denoting the deflections and the rotations of the cross-section of the beam are expressed in polynomial form. Using Lagrange's equations, the problem is reduced to the solution of a system of algebraic equations. The first six eigenvalues of the considered beams are calculated for different thickness-to-length ratios. The results are compared with the previous results based on Timoshenko and Euler-Bernoulli beam theories.
Keywords: free vibrations of beams; the third-order shear deformation theory; Lagrange's equations; Lagrange multipliers; TIMOSHENKO BEAMS; Engineering